Commedia dell'arte - couture edition - Bayern, Franz Herzog von 1933- (Birkhäuser, 2009)
Documents the design and manufacturing processes involved in updating the sixteen porcelain figures of the Commedia dell'Arte, originally created by Franz Anton Bustelli in 1760, for their limited reissue in 2009 by Staatliche Porzellan-Manufaktur Nymphenburg. Includes designs by sixteen internationally renowned fashion designers, including Vivienne Westwood, Christian Lacroix, etc
Keywords: Geschichte 1760-2008; Kleinplastik; Nymphenburger Porzellan; Commedia dell'arte -- Motiv; Bustelli, Franz Anton / 1723-1763 / Adaptations